2016
DOI: 10.1002/cmdc.201600073
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure and Constrained Molecular Dynamics Study of Vitamin B12 Conjugates of the Anorectic Peptide PYY(3–36)

Abstract: Vitamin B12–peptide conjugates have considerable therapeutic potential through improved pharmacokinetic and/or pharmacodynamic properties imparted on the peptide upon covalent attachment to vitamin B12 (B12). There remains a lack of structural studies investigating the effects of B12 conjugation on peptide secondary structure. Determining the solution structure of a B12–peptide conjugate or conjugates and measuring functions of the conjugate(s) at the target peptide receptor may offer considerable insight conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 41 publications
(72 reference statements)
0
9
0
Order By: Relevance
“…Hence, the structural tolerance of the binding proteins toward Cbl conjugates require further exploration. Current structural criteria concerning the efficient delivery of Cbl conjugates are qualitative, mostly rely on computed structures, and lack deeper insights from experimental studies.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the structural tolerance of the binding proteins toward Cbl conjugates require further exploration. Current structural criteria concerning the efficient delivery of Cbl conjugates are qualitative, mostly rely on computed structures, and lack deeper insights from experimental studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, the structure of the ligand‐binding site remained approximately unchanged and rigid, attributed to the fact that both quercetin and quercitrin were bound to the internal cavity of BLG by one and three hydrogen bond interactions, respectively. Similarly, the hydrogen bonding interaction also dominated the conjunction between vitamin B 12 and anorectic peptide unstructured region (residues 3 to 10; Henry et al., ); whereas they observed that the conjugation of vitamin B 12 with anorectic peptide caused the small change in secondary structure of the peptide. During the flavonol–human salivary protein interaction, binding of quercetin 3‐ O ‐glucoside to the IB937 model peptide caused the local structural rearrangement (Ferrer‐Gallego et al., ).…”
Section: Simulations To Evaluate the Dynamic Behaviors Of Componenmentioning
confidence: 99%
“…The dietary uptake pathway of cobalamin can be utilized to deliver the truncated form of the anorectic peptide tyrosine-tyrosine (PYY 3–36 ) to its target receptor . Henry et al investigate the effect of conjugation of cyancobalamin and PYY 3–36 , blending in experiment and computations . The crystallographic structure of cobalamin is taken from its complex with TC (2BB5).…”
Section: General Information and Computational Modeling Of Cell Surfa...mentioning
confidence: 99%
“…The group of Doyle acquires the needed additional parameters for the ligand (and insulin binding bridge) and justly relies on GROMOS for transcobalamin. The same set is used for description of the Cbl complex with PYY 3–36 . AMBER is the preferred option for the Cbl-PNA conjugate (with Cbl-related parameters from the literature) and for the wild type and mutated apo-TC in the study of Silla et al This is also a good choice, taking into account the presence of a nucleic acid moiety in the simulations.…”
Section: General Information and Computational Modeling Of Cell Surfa...mentioning
confidence: 99%